2002
DOI: 10.1152/japplphysiol.01035.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Hypothermic protection of the ischemic heart via alterations in apoptotic pathways as assessed by gene array analysis

Abstract: Hypothermia improves resistance to ischemia in the cardioplegia-arrested heart. This adaptive process produces changes in specific signaling pathways for mitochondrial proteins and heat-shock response. To further test for hypothermic modulation of other signaling pathways such as apoptosis, we used various molecular techniques, including cDNA arrays. Isolated rabbit hearts were perfused and exposed to ischemic cardioplegic arrest for 2 h at 34 degrees C [ischemic group (I); n = 13] or at 30 degrees C before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 29 publications
6
72
0
2
Order By: Relevance
“…It has been shown that mild hypothermia can prevent ischemic cells from entering apoptosis through prevention of mitochondrial dysfunction and inhibition of caspase release [25][26][27]. Moreover, hypothermia has been shown to improve ion homeostasis, decrease free radical formation, stabilize cellular membranes and prevent intracellular acidosis [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that mild hypothermia can prevent ischemic cells from entering apoptosis through prevention of mitochondrial dysfunction and inhibition of caspase release [25][26][27]. Moreover, hypothermia has been shown to improve ion homeostasis, decrease free radical formation, stabilize cellular membranes and prevent intracellular acidosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental setting, mild hypothermia has a positive effect on contractility, but deep hypothermia has been associated with deterioration in cardiac function [19,20]. The tissue-protective mechanism of action is multi-factorial and partly unknown [20][21][22][23][24][25][26][27]. We recently found that hypothermia reduces ischemia related coronary t-PA release, suggesting a possible role for t-PA as a mechanism for reperfusion injury that may be affected by hypothermia [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, reduced oxygen demand does not fully explain the positive effects of hypothermia and several additive effects have been suggested [35]. It has been shown that mild hypothermia can prevent ischemic cells from entering apoptosis through prevention of mitochondrial dysfunction and inhibition of caspase release [36][37][38]. Moreover, therapeutic hypothermia has been shown to improve ion homeostasis, suppress ischemia induced inflammatory reactions, decrease free radical formation, stabilize cellular membranes and prevent intracellular acidosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…The first-strand cDNA was synthesized by SuperScript II reverse transcriptase (Invitrogen) at 42°C for 1 h. The reaction was terminated at 70°C for 15 min. 1 µL of the cDNA mixture was used for subsequent PCR (10 µL) with the following primer set: bcl-2 forward, 5'-GTGGCCTTCTTTGAGTTCG-3'; bcl-2 reverse, 5'-CTTCAGAGACAGCCAGGAG-3' (product size 212bp) [16] p53 forward, 5'-ACCTTCCGACACAGCGTGGT-3'; p53 reverse, 5'-CTCCATCCAGCGGCTTCTTC-3' (349bp) [17] glyceraldehyde-3-phosphate dehydrogenase (GAPDH) forward, 5'-ACCACGGTG CACGCCATCAC-3', GAPDH reverse, 5'-TCCACCACCCTGTT GCTGTA-3' (454bp). PCR were conducted with an initial denaturation at 94°C for 5 min followed by 35 cycles (bcl-2 and p53) and 25 cycles (GAPDH) of amplification.…”
Section: Rt-pcr Analysismentioning
confidence: 99%